2019
DOI: 10.1002/adsc.201801319
|View full text |Cite
|
Sign up to set email alerts
|

Food Sweetener Saccharin in Binary Organocatalyst for Bulk Ring‐Opening Polymerization of Lactide

Abstract: Polylactic acid or polylactide (PLA) is the leading commercialized bio-based polyester widely used in biomedical apparatus and disposable food packaging materials, among others. Desirable features of green and environmentally friendly ring-opening polymerization (ROP) of lactide (LA) by organocatalysts were bulk ROP at high temperature; the organocatalyst should be inexpensive, readily available, and biosafe in the produced PLA; and the ROPs should afford PLA of precisely controlled molecular weights with no t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Study showed that DMAP$saccharinate (DMAP$Sac) catalyzed ROP of LLA at a fast rate (Scheme 100). 121 19 Tetrazole-amino-saccharin Tetrazole-amino-saccharin was synthesized from the reaction of saccharyl chloride (synthesized by saccharin) and 2methyl-2(H)-tertrazole-5-amine (derived from tetrazole-5-amine) under inert condition as described Scheme 101(a). 122 An anaerobic oxidation of benzyl alcohols was reported by Frija et al in the presence of tetrazole-amino-saccharin as organocatalyst under solvent free conditions and microwave assisted process comprising aqueous tert-butyl hydroperoxide (TBHP) as oxidant (Scheme 101b).…”
Section: Dmap-saccharinmentioning
confidence: 99%
“…Study showed that DMAP$saccharinate (DMAP$Sac) catalyzed ROP of LLA at a fast rate (Scheme 100). 121 19 Tetrazole-amino-saccharin Tetrazole-amino-saccharin was synthesized from the reaction of saccharyl chloride (synthesized by saccharin) and 2methyl-2(H)-tertrazole-5-amine (derived from tetrazole-5-amine) under inert condition as described Scheme 101(a). 122 An anaerobic oxidation of benzyl alcohols was reported by Frija et al in the presence of tetrazole-amino-saccharin as organocatalyst under solvent free conditions and microwave assisted process comprising aqueous tert-butyl hydroperoxide (TBHP) as oxidant (Scheme 101b).…”
Section: Dmap-saccharinmentioning
confidence: 99%
“…Following the same concept, a recent study used a DMAP and saccharin system 1:1 (DMAP:Sac) as a bifunctional catalyst for the ROP of LLA and δ-valerolactone (VL) in bulk at 140 °C (Figure 4a). 19 They first combined three commercial pyridines including DMAP, phenylpyridine (PPY), and pyridine with a stoichiometric ratio of saccharine. Among them, DMAP:Sac ionic mixture was the most efficient salt in the ROP of LLA.…”
Section: Acs Macro Lettersmentioning
confidence: 99%
“…In this Viewpoint, we summarize the results presented in the literature in the use of a family of thermally stable organocatalysts based on ionic compounds composed of mixtures of organic acids and bases. These catalysts have successfully been used in industrially relevant conditions, requiring high temperatures, both in chain growth and step-growth polymerizations of polyesters, polyesteramides or polyethers. , Moreover, this Viewpoint will also address the recent efforts in the use of these acid–base mixtures in polymer recycling by depolymerization which has nowadays raised significant attention from an economic and environmental perspective . It is worth to mention that we intend to keep the scope of this viewpoint as narrow as possible and it will be solely based on acid–base mixtures prepared by physical interaction (proton transfer reaction) not covering the extensive literature based on frustrated ion pairs, ionic liquids, or acidic ionic liquids as catalyst for polymerizations. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, by use of DMAP and saccharin, a naturally occurring acid, in stoichiometric quantities, the ROP of L-LA provided stereoregular PLLA of moderate molecular weights ( M n = 4 kg mol –1 ) but narrow dispersity at 90 °C. 24 …”
Section: Introductionmentioning
confidence: 99%